Prognostic marker C3AR1 is associated with ovarian cancer cell proliferation and immunosuppression in the tumor microenvironment - Jinfa Huang; Lei Zhou; Kaixian Deng (BMC, 2023)
Abstract Background C3AR1 was reported in driving tumor immunity in multiple cancers. However, its roles in ovarian cancer remain unclear. This study aims to determine role of C3AR1 in prognosis and regulating tumor infiltrating immune cells of ovarian cancer (OC). Materials and methods The expression, prognosis and clinical data related to C3AR1 were collected from public databases such as The Cancer Genome Atlas (TCGA), Human Protein Atlas (HPA) and Clinical Proteomics Tumor Analysis Alliance (CPTAC), and further analyze their relationship with immune infiltration. Immunohistochemistry verified the expression of C3AR1 in ovarian cancer and control tissues. C3AR1 was forced expressed in SKOV3 cells by plasmid transfection, and verified by qRT-PCR and Western blot. Cell proliferation were evaluated by EdU assay. Results Bioinformatics analysis (TCGA, CPTAC) and immunohistochemical staining of clinical samples confirmed higher C3AR1 expression in ovarian cancer than that in normal tissues. High C3AR1 expression predicted adverse clinical outcomes. KEGG and GO analysis showed that the biological processes of C3AR1 in ovarian cancer are mainly involved in T cell activation, cytokine and chemokine activation. C3AR1 expression was positively correlated with chemokines and their receptors in the tumor microenvironment, such as CCR1(R = 0.83), IL10RA (R = 0.92), and INFG (R = 0.74). In addition, increased C3AR1 expression predicted more infiltration of tumor-associated macrophages, dendritic cell and CD8 + T cell. Some important m6A regulators, such as IGF2BP2, ALKBH5, IGFBP3 and METL14, are significantly positively or negatively correlated with C3AR1. Finally, overexpression of C3AR1 significantly increased proliferation of SKOV3 cells. Conclusion In summary, our study suggested that C3AR1 is associated with the prognosis and immune cell infiltration of ovarian cancer, and is a promising immunotherapeutic target.